Women new settlers : groupwork in resettlement : psychodrama with refugee and immigrant women living in Auckland, New Zealand : a thesis submitted in partial fulfilment of requirements for the degree of Master of Philosophy in the School of Social and Cultural Studies, Massey University - Mendelsohn, Estelle (Massey University, 2002)
This research set out to explore whether psychodramatic groupwork was acceptable and useful for refugee and immigrant women resettling in Auckland, New Zealand. Over eighty sessions have been run by the author and her team, for women from many ethnic backgrounds, predominantly from India, Iraq, Iran and Afghanistan. Psychodramatic groupwork run by a multicultural team which offers therapeutic processes relevant to coping with trauma related to premigration and current events had never been offered in New Zealand. The feminist research paradigm used incorporated qualitative methodologies and methods based on what the women brought forth in sessions. The group work which also included creative arts therapies, and contributions from the women, was acceptable and useful to many of the women, based on self-report and team observations. Groupwork for refugee and immigrant women coping with resettlement in New Zealand has rarely been part of policy and service delivery, despite recommendations from United Nations agencies. Gender analysis of government policies is now a requirement for some government departments in New Zealand. There is no such requirement with respect to the Department of Labour which deals with refugee and immigrant women. It is also rare to find such issues addressed in relevant research from non-government sources. A review of literature from several discourses revealed the importance of including gender-sensitive policies and practice for refugee and immigrant women in resettlement. In particular, feminist research indicated that areas of inequity and invisibility that affect women in wider contexts can have even more damaging effects for these groups of women. As women establish themselves in countries such as New Zealand, changes in legislative contexts related to more human rights for women can produce more equity but also more isolation from their ethnic communities. An ecological context model which incorporated dynamic change was evolved to reflect the many variables involved. Key informants supported recommendations for women-only therapeutic groups amongst other services for refugees and immigrants and that such services are not overtly linked to mental health organizations.. Further research is recommended in many domains, including exploration of gendered differences at all contextual levels. Further research on groupwork with refugee women who have suffered many traumas and losses is particularly recommended. Research on the similarities for refugee and immigrant women would also contribute to the field. Such research could be concurrent with provision of well-funded groupwork services with adequate infrastructures to support the work.
Keywords: Drama therapy; Female immigrants; Immigrant women; Immigrants, Auckland; Refugees, New Zealand